Novel approaches for loose bolt detection with and without sensors using heterodyning effect - (:unkn) unknown (DEStech Publications, 2017)
Detection of defects in the early stages of growth and nucleation is very important in structural health monitoring (SHM) applications. Defects, such as delamination, debonding, loose bolts and cracks create nonlinear behavior at the surface response. Different techniques have been developed to identify the transformation of a structure from the linear to the nonlinear state in presence of defect(s). Nonlinear wave modulation spectroscopy (NWMS) based methods were developed to detect the nonlinearity created due to combination of low and high excitation frequencies. The excitation signal of the NWMS method is created by modulating the ultrasonic probe signal with a low frequency vibration. In this study, SHM and sensor-less SHM (SSHM) methods are proposed for detection of loose bolts. The proposed methods rely on the heterodyne effect. The frequencies of the two harmonic excitation signals are not limited to the combination of low and high frequencies. In the presence of loose bolts the structure behaves like a nonlinear system and new frequencies are generated. The new frequencies can be observed at the summation, subtraction, and other harmonics of the excitation frequencies. The new frequencies may be monitored with sensors, similar to conventional SHM systems. It is also possible to select the difference of the excitation frequencies to be lower than 20 kHz (audible frequency range) to create audible alarms. The new SSHM eliminates the need for the sensor(s) and processor(s). The SSHM may be used to make very low cost SHM systems or it can be used as back up when the sensor(s) or the processor(s) of the SHM system fail.